Effect of infill geometry on the structural performance and fracture morphology of FDM-printed PLA composites - Ulkir, Osman; Karadag, Arif (Emerald Group Publishing Ltd, 2026)
PurposeThis study aims to systematically investigate the effect of infill geometry on the mechanical performance and fracture morphology of polylactic acid (PLA)-based materials fabricated by fused deposition modeling (FDM). In particular, the relationship between infill pattern, material type, and microstructural fracture mechanisms is evaluated through combined mechanical testing and scanning electron microscopy (SEM) analysis.Design/methodology/approachThree different PLA-based filaments (pure PLA, PLA/Wood, and PLA/Cf) were printed using seven infill patterns at a constant infill density of 80% and fixed printing parameters. Standard test specimens were prepared according to ASTM D638, D695, and D790 for tensile, compressive, and flexural tests, respectively. A full factorial experimental design was employed, and each test was performed with three repetitions to ensure statistical reliability. SEM observations were conducted at multiple magnifications to examine interlayer bonding, void formation, and crack propagation behavior.FindingsThe results demonstrate that both material type and infill geometry play a dominant role in determining mechanical performance and fracture behavior. Among all configurations, the concentric infill pattern provided the highest mechanical strength for all materials. Pure PLA exhibited the best overall performance, while PLA/Cf showed fracture dominated by interfacial crack propagation. PLA/Wood samples exhibited high porosity, particle pull-out, and premature failure due to weak fiber-matrix adhesion.Originality/valueThis study offers a comprehensive evaluation of material-pattern interaction in FDM by integrating macroscopic mechanical testing with SEM-based fracture analysis. The results provide microstructural evidence explaining performance differences and establish a scientific framework for infill pattern optimization and material selection in performance-oriented applications.
Keywords: Fused Deposition Modeling; Pla Composites; Surface Morphology Analysis; Filling Pattern; Mechanical Properties